Nur77 attenuates inflammatory responses and oxidative stress by inhibiting phosphorylated IκB-α in Parkinson’s disease cell model - Yan, Junqiang (Aging (Albany NY), 2020)
Neuroinflammation and oxidative stress play key roles in the pathological development of Parkinson’s disease (PD). Nerve growth factor-induced gene B (Nur77) is closely related to dopamine neurotransmission, and its pathogenesis is unclear. This study aims to investigate the role and mechanism of Nur77 in a cell model of Parkinson’s disease. Silencing Nur77 with siRNA can aggravate intracellular LDH release, increase the expression of pro-inflammatory genes (such as tumor necrosis factor α, nuclear factor κB (p65), monocyte chemotactic protein 1, interleukin-6), and decrease cell survival, decrease expression of nuclear factor E2-related factor(Nrf2), heme oxygenase 1, NADPH quinineoxidoreductase-1. Cytosporone B (Nur77 agonist) has the opposite effect to Nur77 silencing. PDTC (NF-κB inhibitor / antioxidant) can also inhibit pro-inflammatory genes to a similar degree as Cytosporone B. Phosphorylated IκB-α can be inhibited by Cytosporone B, while silencing Nur77 can increase the protein expression level of phosphorylated IκB-α. After silencing IκB-α, both Cytosporone B and siNur77 did not affect pro-inflammatory genes and antioxidant stress. These findings reveal the first evidence that Nur77 exerts anti-inflammatory and antioxidant stress effects by inhibiting IκB-α phosphorylation expression in a Parkinson cell model. Nur77 may be a potential therapeutic target for Parkinson’s disease.